Raging Sea: Undertow #2 - Buckley, Michael, 1969- (Boston : Houghton Mifflin Harcourt, 2015)
Struggling to survive in a decimated world where nearly everyone she loves is missing or presumed dead, Lyric Walker works to unite the Alpha before a second wave of invasions wipe out the rest of humanity.
Keywords: Survival -- Fiction; Love -- Fiction; Fantasy; Survival skills -- Fiction; Romance fiction; Fantasy fiction